Numerical investigation of trailing edge flow in centrifugal pump impellers - Litfin, Oliver; Delgado, Antonio (13th European Turbomachinery Conference on Turbomachinery Fluid Dynamics and Thermodynamics, ETC 2019, 2019)
In the fields of aerodynamics and turbomachinery trailing edge flows are of great interest as they can substantially affect performance, vibration and sound emission. The present paper discusses the trailing edge and wake flow in centrifugal pump impellers. In the first part of the study the effect of the trailing edge flow on the performance of equiangular impeller blades was investigated by means of 2D steady RANS simulations for a wide range of blade angles and flow coefficients. The effect was quantified by the slip coefficient as a measure for the overall trailing edge flow deflection from the theoretical, inviscid flow through an impeller with an infinite number of blades. For the typical cut-off or knuckle-type trailing edge configuration an attached and a separated flow regime could be identified, mainly depending on the blade angle. Consequently, in the second part of the study, detached-eddy simulations were carried out, revealing the flow structures of the different trailing edge flow regimes in greater detail.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Centrifugal pump; DES; Impeller; Slip factor; Trailing edge